What influences people’s willingness to receive the COVID-19 vaccine for international travel? - Wang, Mingzhuo; Kunasekaran, Puvaneswaran; Rasoolimanesh, S. Mostafa (Routledge, 2021)
Although the hope of restarting international travel is now largely pinned on the COVID-19 vaccine, vaccination hesitancy among travellers remains an obstacle to this endeavour. Therefore, it is imperative to understand the mechanisms that affect people’s attitudes towards receiving the COVID-19 vaccine for international travel. This study contributes to the restart of international travel by proposing an integrated framework of the protection motivation theory (PMT) and the concepts of travel desire and travel vaccination concerns, which can be applied to examine people’s willingness to receive the COVID-19 vaccine for international travel, to design effective intervention strategies to promote vaccination rate.